Editorial: refractory reflux sensitivity—A place for baclofen? Authors' reply. Issue 4 (25th July 2022) - Raymenants, Karlien; Tack, Jan
Abstract : LINKED CONTENT This article is linked to Pauwels et al papers. To view these articles, visit https://doi.org/10.1111/apt.17068 and https://doi.org/10.1111/apt.17103